2017
DOI: 10.1152/ajpgi.00428.2016
|View full text |Cite
|
Sign up to set email alerts
|

A small population of liver endothelial cells undergoes endothelial-to-mesenchymal transition in response to chronic liver injury

Abstract: Rising evidence points to endothelial-to-mesenchymal transition (EndMT) as a significant source of the mesenchymal cell population in fibrotic diseases. In this context, we hypothesized that liver endothelial cells undergo EndMT during fibrosis progression. Cirrhosis in mice was induced by CCl A transgenic mouse expressing a red fluorescent protein reporter under the control of Tie2 promoter (Tie2-tdTomato) was used to trace the acquisition of EndMT. Sinusoidal vascular connectivity was evaluated by intravital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 44 publications
3
42
0
Order By: Relevance
“…Their direct contribution is due to the synthesis of laminin and collagen in response to TGFβ1 after sustained injury [159]. Whether endothelial cells generated from endothelial-to-mesenchymal transition [160] may contribute to ECM deposition remains a field of research.…”
Section: Loss Of Anti-fibrotic Capacitiesmentioning
confidence: 99%
“…Their direct contribution is due to the synthesis of laminin and collagen in response to TGFβ1 after sustained injury [159]. Whether endothelial cells generated from endothelial-to-mesenchymal transition [160] may contribute to ECM deposition remains a field of research.…”
Section: Loss Of Anti-fibrotic Capacitiesmentioning
confidence: 99%
“…Even if liver ECs underwent EndMT in vivo, their population would be very small, as also indicated by Ribera et al (30) results and ours may come from the difference of the study subjects, i.e., humans and mice. It should be mentioned that the same group of researchers recently showed the zonation pattern of hepatic stellate cells (HSCs), which was conserved between healthy and fibrotic mouse livers (3) .…”
Section: We Found Both Vegf Receptor Kdr and Co-receptor Nrp1 Were Momentioning
confidence: 52%
“…Several studies reported that LSECs undergo EndMT in response to chronic liver injury (30)(31)(32) . In contrast, we did not find notable increases in mesenchymal markers, such as Figure 6).…”
Section: Endothelial-to-mesenchymal Transition (Endmt)mentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding liver fibrosis, patients and mice with liver cirrhosis bear a modest but still noticeable subpopulation of liver endothelial cells that express both CD31 and α-SMA. Moreover, when mice with liver cirrhosis were treated with BMP-7 (which prevents cultured murine liver endothelial cells from undergoing TGF-β1-induced EndoMT), their liver fibrosis improved [62].…”
Section: Endomt-derived Myofibroblasts In Other Soft Tissue Fibrosesmentioning
confidence: 99%